Engineering Periodic Dinuclear Lanthanide‐Directed Networks Featuring Tunable Energy Level Alignment and Magnetic Anisotropy by Metal Exchange (Small 22/2022). Issue 22 (2nd June 2022) - Moreno, Daniel; Parreiras, Sofia O.; Urgel, José I.; Muñiz‐Cano, Beatriz; Martín‐Fuentes, Cristina; Lauwaet, Koen; Valvidares, Manuel; Valbuena, Miguel A.; Gallego, José M.; Martínez, José I.; Gargiani, Pierluigi; Camarero, Julio; et al.
Abstract : Lanthanide Multinuclear Networks In article number 2107073, Sofia O. Parreiras, David Écija, and co‐workers demonstrate the tuning of the electronic and magnetic properties of dinuclear lanthanide metal–organic networks by metal exchange while preserving the same structural architecture. The exchange between Er and Dy metallic centers leads to a shift in the energy level alignment and allows the tailoring of both the intensity and orientation of magnetic anisotropy.